Association between Fluid Balance and Treatment Outcome of Ibuprofen for Patent Ductus Arteriosus in Preterm Infants - Chang Liu; Yuan Shi (Reviews in Cardiovascular Medicine, 2023)
Background: Excessive fluid intake is a predictor of the development of patent ductus arteriosus (PDA) in preterm infants. Previous studies have examined the relationship between fluid intake and outcomes following ibuprofen for PDA. However, there is a lack of data to determine whether fluid balance has an effect on ibuprofen treatment for PDA. Therefore, this study sought to determine the relationship between fluid balance and outcomes following treatment with ibuprofen for PDA. Methods: We conducted a retrospective study of 110 infants admitted to the Children’s Hospital of Chongqing Medical University between January 2017 and April 2022, who were treated with ibuprofen for hemodynamically significant PDA (hsPDA). We calculated the average fluid balance before and during the two courses of ibuprofen treatment and whether they were significantly associated with outcomes in hsPDA patients. Results: In the first course of ibuprofen treatment (FIT), responders had lower fluid balance before FIT compared to non-responders [median 31.82 (18.01, 39.66) vs 34.68 (25.31, 43.56) mL/kg/day; p = 0.049], while the fluid balance during FIT [median 40.61 (33.18, 63.06) vs 42.65 (30.02, 57.96) mL/kg/day; p = 0.703] did not differ between responders and non-responders. Fluid balance before the second course of ibuprofen treatment (SIT) (mean 41.58 ± 14.26 vs 35.74 ± 10.99 mL/kg/day; p = 0.322) and during SIT (mean 39.21 ± 12.65 vs 37.00 ± 21.38 mL/kg/day; p = 0.813) was not found to have a significant association with SIT outcome. Multivariate logistic regression analysis showed fluid balance before FIT was a predictor for FIT success [Odds ratio (OR): 0.967; 95% confidence interval (CI): 0.935–0.999; p = 0.042]. Fluid balance within the first week of life had a greater association with the FIT outcome (OR: 0.967, 95% CI: 0.939–0.996, p = 0.027). Gestational diabetes mellitus and higher Apgar scores decreased the possibility of PDA closure after FIT. Conclusions: Lower fluid balance before FIT, especially within the first week of life appeared to be a predictor for closure of hsPDA after FIT in preterm infants.